Uncertainty and Hyperbolic Discounting - Dasgupta, Partha; Maskin, Eric (American Economic Review, 2005)
We propose an evolutionary explanation for the pattern of intertemporal preference reversals often ascribed to hyperbolic discounting. We take the view that preferences—manifested, for example, in urges, cravings, and inclinations— are the outcome of evolutionary forces, and so will induce animals or humans to make survival-maximizing choices in decision problems. We show that if the typical problem involves payoffs whose realization times are uncertain, then optimal preferences give rise to relatively patient behavior when the time horizon is long but induce a switch to impatience when the horizon grows short. Such reversals do not entail dynamic inconsistency in typical decision problems; behavior there is optimal. However, if a decision-maker is confronted with a choice for which the realization-time uncertainty falls outside the evolutionary norm, her preferences may well prompt her to behave inconsistently. We argue that, if such a choice problem recurs, her evolutionarily endowed aability to learn will lead her to make self-commitments against these urges.(This abstract was borrowed from another version of this item.)